2005
DOI: 10.1007/s11177-005-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Reproduction Biotopes on the Genetic Differentiation of Populations of Sockeye Salmon Oncorhynchus nerka

Abstract: Variation of mitochondrial DNA (mtDNA) was examined in nine populations from three lake-river systems of Chukotka and Kamchatka. Significant differences were found between most of the sockeye salmon samples studied. The genetic differences among populations were not high and often did not correlate with the geographical distances between them. The low population divergence is explained by a short time of existence of most of them, having been formed after the recession of the upper Pleistocene glacier. When th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…It can be assumed that the lower parts of the Kamchatka River were inhabited by fish from other refugia during their expansion after the glacier retreat in the Late Quaternary. Our data are in agreement with the results obtained previously on the sockeye salmon from a number of lake-river systems of Kamchatka and Chukotka (Brykov et al, 2005), indicating the different refugia origin of populations.…”
Section: F I G U R Esupporting
confidence: 92%
See 4 more Smart Citations
“…It can be assumed that the lower parts of the Kamchatka River were inhabited by fish from other refugia during their expansion after the glacier retreat in the Late Quaternary. Our data are in agreement with the results obtained previously on the sockeye salmon from a number of lake-river systems of Kamchatka and Chukotka (Brykov et al, 2005), indicating the different refugia origin of populations.…”
Section: F I G U R Esupporting
confidence: 92%
“…Literature and our results (Bachevskaya et al, 2013(Bachevskaya et al, , 2015Brykov et al, 2005;Khrustaleva, 2016) Haplotypes of both haplogroups are found in approximately the same proportion in Lake Azabachye, located in the lower reach of the Kamchatka River, as in other river basins of the Asian coast. It can be assumed that the lower parts of the Kamchatka River were inhabited by fish from other refugia during their expansion after the glacier retreat in the Late Quaternary.…”
Section: F I G U R Esupporting
confidence: 74%
See 3 more Smart Citations